Popliteal Cysts in Paediatric Patients: Clinical Characteristics and Imaging Features on Ultrasound and MRI. (5th May 2011) - Neubauer, Henning; Morbach, Henner; Schwarz, Tobias; Wirth, Clemens; Girschick, Hermann; Beer, Meinrad
Abstract : Popliteal cysts, or Baker cysts, are considered rare in children and may exhibit particular features, as compared with adults. We studied data from 80 paediatric patients with 55 Baker cysts, examined over a period of 7 years, and correlated clinical presentation with findings on ultrasonography and MRI. Prevalence of popliteal cysts was 57% in arthritic knees, 58% with hypermobility syndrome, and 28% without risk factors. Only one patient had a trauma history and showed an ipsilateral cyst. Mean cyst volume was 3.4 mL; cysts were larger in boys. Patients with arthritis had echogenic cysts in 53%. Cyst communication with the joint space was seen in 64% on ultrasonography and 86% on MRI. In conclusion, Baker cysts are a common finding in a clinically preselected paediatric population. Children with Baker cysts should be assessed for underlying arthritis and inherited joint hypermobility, while sporadic Baker cysts appear to be common, as well.